Improved Pharmacokinetics of Icariin (ICA) within Formulation of PEG-PLLA/PDLA-PNIPAM Polymeric Micelles - Lu-Ying Han; Yun-Long Wu; Chun-Yan Zhu; Cai-Sheng Wu; Chun-Rong Yang (Pharmaceutics, 2019)
Icariin (ICA) is a major flavonoid that contains the active compound Epimedii Folium. However, ICA’s pharmacokinetic characteristics remain unsatisfactory due to its low bioavailability, and hence limited drugability. In order to improve its pharmacokinetics and achieve prolonged blood circulation time, a novel polymeric micelle, made of the self-assembled micelle between poly (ethylene glycol)-poly (L-lactic acid) (PEG-PLLA) and poly (D-lactic acid)-poly(N-isopropylacrylamide) (PDLA-PNIPAM), was designed to encapsulate ICA. Our experimental results showed that this polymeric micelle formulation of ICA exhibited uniform nano-size distribution and high stability within 48 h. The new formulation also allowed sustained ICA release in an in vitro drug release study. Furthermore, in vivo experiments revealed that ICA bioavailability in the PEG-PLLA/PDLA-PNIPAM polymeric micelle formulation was significantly higher compared to ICA alone, or ICA in the traditional Pluronic F127 micelle formulation. Finally, we show that metabolite analysis confirmed that ICA within the PEG-PLLA/PDLA-PNIPAM polymeric micelle formulation provided better drug protection, reduced drug metabolites production, and decreased undesired first-pass effects. Overall, these data show that ICA within PEG-PLLA/PDLA-PNIPAM polymeric micelle formulation exhibit advantages, in terms of improved physicochemical properties, sustained release of ICA in vitro, and improved bioavailability of ICA in vivo, which represent a feasible approach for improving the drugability of pharmaceutical small molecules with low bioavailability or poor stability.